Genetic diversity among Palestinian fig varieties (Ficus carica L.) using ISSR, and RAPD markers - Ayat Khaled Mubaslat (My University, 2012)
The genetic diversity in Palestinian fig (Ficus carica L.), was studied using random amplified polymorphic DNA (RAPD) and inter simple sequence repeats (ISSR) markers. Twenty three fig accessions (20 common fig cultivars, and two more wild types and one San pedro type (Dafor) crossponding to the main cultivated varieties in Palestine were analyzed. The cultivars were assessed using the randomly amplified polymorphic DNA (RAPD) technique. The 21 out of 25 screened markers showed reproducible polymorphic profiles. The generated 1518 data entries were analyzed among which 420 entries were for present bands and 1098 for absent bands. After determining Jaccard similarity index, some genotypes showed high genetic similarity (77%) was recorded between Zraqi and Ghzali, while other were less similar (0% between Ajloni and Qraee). Moreover, the primers were evaluated for their resolving power, where primer OPH08 achieved the highest power 3.16 meanwhile the weakest power was shown by primer OPA03 (0.15). Furthermore , dendrogram was elaborated by cluster analysis according to the UPGMA algorithm . The genotypes were clustered into seven clades . The mean number of amplification RAPD bands (6.7) was little more than that of ISSR (5.57). Moreover, the total number of polymorphic bands (161) detected by RAPD primers was much higher than that of the ISSR primers (69), which suggested that the RAPD markers were more powerful compared to ISSR markers in the capacity of revealing more informative bands in a single amplification.

اجريت هذه الدراسة لتحديد التنوع الوراثي في الصفات الجينية ل 23 صنفا من أصناف التين (Ficus carica L. ) ( 20 صنفا محليا مشهورا وصنفين بريين وصنف واحد اجنبي) ممثلة للاصناف الموجودة في فلسطين ، باستخدام آليات التضخم العشوائي متعدد الأشكال للحمض النووي الرايبوزي (RAPD)، وجملة تكرار التسلسل البسيط (ISSR). 21 كاشفا وراثيا من اصل 25 كاشف استخدمت في الدراسة اظهرت انماطا مختلفة من حزم مضاعفة DNA . وصل عدد مدخلات تقنية RAPD التي تم تحليلها نحو 1518، كان من ضمنها 420 لحزم DNA الموجودة (1)، و 1098 لحزم DNA غير الموجودة (0). وبحساب معامل التشاظهرت بعض الاصناف تشابها كثيرا بنسبة 77% بين زراقي وغزالي بينما لم يظهر بعض الاصناف أي نوع من التشابه كما في الصنفين عجلوني وقراعي . قيمت الكاشفات بحساب قيمة Rp لها فأظهر الكاشف OPH08 اعلى قيمة 3.16 بينما كانت15 . اقل قيمة للكاشف OPA03 . كما وتم حساب المسافات الجينية بين الاصناف باستخدام معامل تشابه النرد Dendrogram بالاعتماد على تحليل الكتلة.UPGMAو كانت حزم DNA الناتجة باستخدام RAPD موزعة على سبعة مجموعات اساسية. وكان متوسط عدد حزم التضاعف باستخدام ألية RAPD (6.7) أكثر قليلا من تلك باستخدام آلية ISSR (5.57). وعلاوة على ذلك، فإن العدد الإجمالي للحزم المتضاعفة متعددة المظهر باستخدام RAPD (161 حزمة) أعلى بكثير من تلك الناتجة باستخدام آلية ISSR (69 حزمة). الأمر الذي يشير إلى أن ألية استخدام RAPD كانت أكثر كفاءة من آلية ISSR من خلال عدد حزم DNA المتضاعفة في التفاعل الواحد.
التنوع الجيني في مجموعة التين الفلسطينية باستخدام تقنيتي ٌRAPD وISSR